Digital Health Literacy and the Influence of Social Media Information Quality on Childbirth Decision-Making among Pregnant Women - Khayru, Rafadi Khan (Bulletin of Science, Technology and Society, 2025)
This paper investigates the relationship between digital health literacy and the interpretation and utilization of social media information by pregnant women in selecting childbirth methods. Employing a qualitative literature review and thematic synthesis, the analysis shows varying levels of digital health literacy significantly modulate women’s abilities to discern credible from unreliable information within rapidly evolving digital contexts. The findings reveal that high-quality, evidence-based content fosters informed decision-making aligned with contemporary medical standards, while exposure to low-quality, anecdotal, or biased narratives can lead to misconceptions, anxieties, and suboptimal childbirth choices. Socioeconomic factors and prior health education influence susceptibility to digital misinformation. The study found the necessity for synergistic efforts across healthcare, education, and regulatory domains to elevate digital health literacy and ensure the availability of accurate content for expectant mothers. Integrating digital health literacy into antenatal care, promoting clinician engagement in online forums, and establishing clear content moderation guidelines are pragmatic responses to the identified challenges. Such systemic interventions are critical to empowering maternal autonomy and protecting maternal and neonatal health in an increasingly digitalized world.